昭和基地における気象衛星データの受信方法(g.将来計画)(第2回極域における電離圏磁気圏総合観測シンポジウム : Part II) - 田中, 信也; タナカ, シンヤ; Tanaka, Shinya; 芳野, 赳夫; ヨシノ, タケオ; Yoshino, Takeo (国立極地研究所, 1980)
1979年からGARPの副計画としてPOLEXが3年間実施され,1982年からはMAPが開始される.これらの計画に基づいて,第21次南極地域観測隊により昭和基地に気象衛星受信装置を設置し観測を開始する.これによって地表面温度分布,雲分布,垂直温度分布,オゾン分布等の情報を取得し,極地の中高層大気循環,春期における極地成層圏突然昇温の発生機構,極地における気象の全体像等を解明し,さらに地球における大気構造とその変化,および極地中高層大気がそれに及ぼす影響等に関して解明できるものと期待している. POLEX program, as a sub-project of GARP, will start the 3 years' observation from 1979. And MAP will be opened from 1982. Based on these projects, the 21 st Japanese Antarctic Research Expedition will be set up with the meteorological satellite tracking and telemetry system at Syowa Station in Antarctica, and will receive the information of surface temperature, cloud, ozone and vertical temperature profiles. The analytic result of described information will make clear the circulation of the atmosphere, sudden warming in the spring, structure of a high latitude atmosphere, and the influence of middle upper atmosphere in the polar region affecting the general circulation of the earth's atmosphere. departmental bulletin paper